From lab to market: An integrated bioprocess design approach for new‐to‐nature biosurfactants produced by Starmerella bombicola. Issue 5 (4th February 2018) - Van Renterghem, Lisa; Roelants, Sophie L.K.W.; Baccile, Niki; Uyttersprot, Katrijn; Taelman, Marie Claire; Everaert, Bernd; Mincke, Stein; Ledegen, Sam; Debrouwer, Sam; Scholtens, Kristel; Stevens, Christian; Soetaert, Wim
Abstract: Glycolipid microbial biosurfactants, such as sophorolipids (SLs), generate high industrial interest as 100% biobased alternatives for traditional surfactants. A well‐known success story is the efficient SL producer Starmerella bombicola, which reaches titers well above 200 g/L. Recent engineering attempts have enabled the production of completely new types of molecules by S. bombicola, e.g. the bolaform SLs. Scale‐up of bolaform SL production was performed at 150 L scale. The purified product was evaluated in detergent applications, as classic SLs are mostly applied in eco‐friendly detergents. In this paper, we show that they can be used as green and non‐irritant surfactants in for example (automatic) dishwashing applications. However, due to the presence of an ester function in the biosurfactant molecule a limited chemical stability at higher pH values (>6.5) was noticed, (therefore called 'non‐symmetrical' (nsBola)) which, is a major drawback that will most likely inhibit market introduction. An integrated bioprocess design (IBPD) strategy was thus applied to resolve this issue. The strategy was to replace the fed fatty acids with fatty alcohols, to generate so‐called "symmetrical bolaform (sBola) sophorosides (SSs), " containing two instead of one glycosidic bond. Next to a change in feeding strategy, the blocking of the fatty alcohols from metabolizing/oxidizing through the suggested ω‐oxidation pathway was necessary. For the latter, two putative fatty alcohol oxidase genes ( fao1 and fao2 ) were identified in the S. bombicola genome and deleted in the bolaform SL producing strain ( ΔatΔsble ). Shake flask experiments for these new strains ( ΔatΔsbleΔfao1 and ΔatΔsbleΔfao2 ) were performed to evaluate if the fed fatty alcohols were directly implemented into the SL biosynthesis pathway. Indeed, sBola sophorosides (SSs) production up to 20 g/L was observed for the ΔatΔsbleΔfao1 strain. Unexpectedly, the Δ at Δ sble Δ fao2 strain only produced minor amounts of sBola sophorosides (SSs), and mainly nsBola SLs (alike the parental Δ at Δ sble strain). The sBola sophorosides (SSs) were purified and their symmetrical structure was confirmed by NMR. They were found to be significantly more stable at higher pH, opening up the application potential of the biosurfactant by enhancing its stability properties. Abstract : In this paper, Van Renterghem et al. (2017) scale up the production of a newly discovered glycolipid microbial biosurfactant, namely bolaform SLs. After purification, the application potential was assessed and this unravels very interesting results. However, due to its lower chemical stability and therefore limiting its application potential, the production is redirected towards a more stable biosurfactant by applying an integrated bioprocess design strategy. The latter has proven to be key to bring microbial biosurfactants closer to the market.